Coming face to face with innovation and digitization: the case of book printing in Spain - Magadán Díaz, Marta; Rivas García, Jesús Israel (Journal of print and media technology research, 2021)
This paper deals with how technological change and digitization in the Spanish book printing sector are challenging existing business models and encouraging printers to modify their product portfolio and core competencies. This research analyzes the impact of digitization on the business models of Spanish book printing houses. The case studies conclude that: a) hook printing houses, although aware of the necessary digital transformation, continue to maintain the traditional business model alongside the new one, b) customers are the main driving force for digital transformation in book printing houses, c) there is a trade-off between cultural and environmental policies as drivers of the paradigm shift in book printing houses and d) the digital context is a motivating factor for book printing houses to integrate vertically downstream.
Keywords: core competences; cultural policy; digital transformation; book printing house; business model; Emerging; Scopus